Influence of soil flexibility and plan asymmetry on seismic behaviour of soil-piled raft-structure system. (October 2021) - Bhattacharjee, Tanumoy; Chanda, Diptesh; Saha, Rajib
Abstract: Ever-increasing scarcity of land and demand for high-rise structures has significantly contributed to the use of combined piled raft foundations (CPRF) in soft ground. However, utility, design constraints and aesthetic considerations bring asymmetry to superstructures, making structures more vulnerable during seismic excitations. Traditional design practices involve designing superstructure elements and foundation considering fixity at the base of the superstructure and ignoring soil-structure interaction (SSI) which may result in under-estimation of forces and displacement in the system. Hence, the present study aims at developing new seismic design guideline pertaining to asymmetric single and multi-storied structure supported on CPRF embedded in soft clay. Some important parameters, such as torsional coupling mode of vibration and multi-storey idealisation involving the effect of higher modes are investigated incorporating seismic SSI effect. The study broadly reveals that the torsional to lateral period ratio considerably influence the seismic response of asymmetric structural system on the piled raft foundation due to the incorporation of SSI. Furthermore, multi-storey building idealisation gives a higher estimation of response compared to single storey idealization in superstructure and pile head which may be due to the effect of higher modes of vibration and SSI